Serious Coronary Thrombosis and Pulmonary Artery Thrombosis Revealing Behçet’s Disease - Di LIU; Wangbin NING; Xiaoxia ZUO (Archives of Rheumatology, 2018)
Behçet’s disease is a multisystem inflammatory disorder. Cardiovascular involvement is rare but may present with various manifestations, resulting in high mortality. In this article, we report a young male who had chest pain accompanied by systemic involvement, and was diagnosed of Behçet’s disease with serious pulmonary artery and coronary thrombosis by systemic check-up. Finally, the patient was successfully treated with a combination of prednisone and immunosuppressive agents instead of surgery. To our knowledge, this is the first report of concurrent coronary thrombosis and pulmonary artery thrombosis in Behçet’s disease patients.